Large-Scale and Full-Scale Methods for Examining Wind Effects on Buildings - Gregory A. Kopp (Frontiers Research Topics, 2018)
Global economic losses due to severe weather events have grown dramatically over the past two decades. A large proportion of these losses are due to severe wind storms such as tropical cyclones and tornadoes, which can cause destruction to buildings, houses, and other infrastructure over large areas. To address the growing losses, many new large-scale and full-scale laboratories have been developed. These tools are used to examine the issues that could not be solved with the traditional tools of wind engineering including model-scale boundary layer wind tunnels, simplified standardized product tests, and other methods of analysis. This book presents state-of-the-art results from the development of the many novel approaches being used to mitigate natural disasters around the world.